2022
DOI: 10.3390/nano12091445
|View full text |Cite
|
Sign up to set email alerts
|

A Star Polyamine-Based Nanocarrier Delivery System for Enhanced Avermectin Contact and Stomach Toxicity against Green Peach Aphids

Abstract: The unscientific application of synthesized/botanical pesticides has not only brought the resistance of plant pathogens and pests, but also led to serious environmental pollution. In recent years, various nano-delivery systems have been used for the development of environmental-friendly pesticides with improved efficacy. Herein, the current study constructed an efficient avermectin B1a (AVM) nano-delivery system based on a star polyamine (SPc) and focused on the characterization and bioactivity of SPc-loaded A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
5
12
0
Order By: Relevance
“…Based on the chemical structures, the negatively charged fluoride groups in lufenuron might combine with the tertiary amines of the SPc. Consistent with previous studies, the positively charged SPc can assemble with thiamethoxam and osthole through electrostatic interaction. , For instance, the putative combining sites might be the positively charged tertiary amines in the SPc with negatively charged nitro groups in thiamethoxam or oxygen groups in osthole. , Meanwhile, the self-assembly of the matrine/SPc, avermectin/SPc, and thiocyclam/SPc complexes is through different interaction forces such as hydrogen bonds and hydrophobic association, ,, and various interaction forces of the SPc with exogenous agents are beneficial for expanding the application field of the SPc.…”
Section: Resultssupporting
confidence: 81%
“…Based on the chemical structures, the negatively charged fluoride groups in lufenuron might combine with the tertiary amines of the SPc. Consistent with previous studies, the positively charged SPc can assemble with thiamethoxam and osthole through electrostatic interaction. , For instance, the putative combining sites might be the positively charged tertiary amines in the SPc with negatively charged nitro groups in thiamethoxam or oxygen groups in osthole. , Meanwhile, the self-assembly of the matrine/SPc, avermectin/SPc, and thiocyclam/SPc complexes is through different interaction forces such as hydrogen bonds and hydrophobic association, ,, and various interaction forces of the SPc with exogenous agents are beneficial for expanding the application field of the SPc.…”
Section: Resultssupporting
confidence: 81%
“…Our results revealed that there was a strong hydrogen bonding and Van der Waals forces between CNAP and SPc, and we deduced the amide NH of CNAP and carbonyl groups or tertiary amines of SPc played an important role in the self-assembly of CNAP/SPc complex. Consistent with previous studies, the SPc can assemble with dinotefuran, monosultap, avermectin and chitosan through hydrogen bond and Van der Waals forces [ 25 , 32 , 33 , 57 ]. Meanwhile, the SPc can also combine with thiocyclam, eugenol, thiamethoxam, matrine and osthole through different interaction forces, such as electrostatic interaction and hydrophobic association [ 25 , 29 , 30 , 31 , 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…Compared to CNAP alone, the complexation of CNAP with SPc formed smaller particles with irregular shape, and the morphology and particle size of SPc-loaded pesticides are not only related to the chemical structures of pesticide and SPc, but also the interaction between pesticide and SPc. Meanwhile, the nanometerization of SPc-loaded CNAP in aqueous solution was similar to our previous studies that the complexation with SPc could decrease the particle sizes of insecticides, such as avermectin, dinotefuran and matrine down to nanoscale [29,32,57]. For instance, the particle size of matrine can be reduced from 858 to 9 nm with the help of SPc, and self-assembly of thiamethoxam/SPc complex can decrease the particle size of thiamethoxam from 576 to 116 nm [29,31].…”
Section: Discussionsupporting
confidence: 84%
“…62 An efficient AVM nanodelivery system based on a star polyamine (SPc) was constructed by Yang et al , which could enhance the contact and stomach toxicity of AVM against green peach aphids, which reveals the wide applications in the agricultural field. 73 Gao et al designed a pH-responsive organic–inorganic hybrid nanomaterial by modifying HMSNs with high adhesion and wettability on rice leaves, 63 which could significantly improve the photostability of AVM and exhibit the high release rate to achieve the high activity of Lepidoptera pests.…”
Section: The Main Categories Of Nanobiopesticides and Their Research ...mentioning
confidence: 99%